2008
DOI: 10.1111/j.1365-2672.2008.03975.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel finding thatStreptomyces clavuligeruscan produce the antibiotic clavulanic acid using olive oil as a sole carbon source

Abstract: Aims:  This study aims to establish whether commercially available food oils can be used by Streptomyces clavuligerus as sole carbon sources for growth and clavulanic acid production. Methods and results:  Batch cultures in bioreactors showed that Strep. clavuligerus growth and clavulanic acid yields in a P‐limited medium containing 0.6% (v/v) olive oil were respectively 2.5‐ and 2.6‐fold higher than in a glycerol‐containing medium used as control. Glycerol‐ and olive oil‐grown cells present different macromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Different vegetable oils may stimulate the production of clavulanic acid, as demonstrated by two different studies. In batch fermentation, Efthimiou et al ( 2008 ) described increased clavulanic acid production when olive oil was used in place of glycerol as a sole carbon source; with a maximum concentration of 47 mg/L being recorded, which is nearly double that observed in media containing glycerol (25 mg/L). These results were consistent with another recent study, whereby the addition of olive oil improved clavulanic acid production as compared to glycerol; with a maximum concentration at 1120 and 564 mg/L, respectively (Salem-Berkhit et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different vegetable oils may stimulate the production of clavulanic acid, as demonstrated by two different studies. In batch fermentation, Efthimiou et al ( 2008 ) described increased clavulanic acid production when olive oil was used in place of glycerol as a sole carbon source; with a maximum concentration of 47 mg/L being recorded, which is nearly double that observed in media containing glycerol (25 mg/L). These results were consistent with another recent study, whereby the addition of olive oil improved clavulanic acid production as compared to glycerol; with a maximum concentration at 1120 and 564 mg/L, respectively (Salem-Berkhit et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on literature obtained in this study, glycerol was found to be the most popular choice of carbon source in clavulanic acid production; in order to ensure an efficient supply of glyceraldehyde-3-phosphate Once glycerol is metabolized into glyceraldehyde-3-phosphate, it can either enter the clavulanic acid biosynthesis pathway, or be involved in glycolytic or gluconeogenesis reactions (Figure 3 ). The inclusion of glycerol enhances the production of clavulanic acid as compared to carbohydrates, as glycerol provides a higher energy content on a weight-by weight basis (Efthimiou et al, 2008 ). As glycerol serves as a backbone for triglycerides, its utilization by S. clavuligerus has prompted researchers to study the potential of other oils to be used as a source of carbon.…”
Section: Discussionmentioning
confidence: 99%
“…Oils are preferred in terms of energy, as they contain approximately 2.4 times the energy of glucose [ 57 ]. Several authors have reported that oils may stimulate CA production [ 93 , 99 , 109 , 110 , 111 , 112 , 113 ]. Lee and Ho [ 109 ] identified palm and palm-kernel oils as the most suitable carbon sources for growth of S. clavuligerus and CA production.…”
Section: Production Of β-Lactamase Inhibitorsmentioning
confidence: 99%
“…Efthimiou et al [ 112 ] described an increase in CA production when 47 mg/L olive oil was used instead of 25 mg/L glycerol as the sole carbon source. In a similar study on the effects of different vegetable oil-based media on cell growth and CA production during S. clavuligerus ATCC 27064 cultivation, Salem-Berkhit et al observed that three out of eight tested oils supported CA production [ 99 ] and that the olive oil-containing medium ensured a CA concentration twice as high as glycerol-containing medium.…”
Section: Production Of β-Lactamase Inhibitorsmentioning
confidence: 99%
“…Although CA is produced by several species of Streptomyces ( Butterworth, 1984 ), its industrial production is almost entirely dependent on S. clavuligerus cultivation in complex medium ( Silva et al , 2012 ). In view to produce clavulanic acid by S. clavuligerus , several components of industrial culture media such as starch and other carbohydrates are not essential ( Efthimiou et al , 2008 ), therefore alternative carbon sources are evaluated to synthesize this antibiotic. Lee and Ho (1996) obtained the highest productivity employing palm oil as carbon source, but other carbons sources such as maltose and dextrin were successfully employed ( Pruess and Kellett, 1983 ).…”
Section: Introductionmentioning
confidence: 99%